Women’s voices in relation to fate, cultural practices and life satisfaction: A case study of Sarawakian single mothers in Samarahan, Sarawak. - Nor Ba’yah Abdul Kadir; Kamsiah Ali (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2012)
This paper describes the women‟s feelings on religious beliefs in relation to fate, cultural practices and life satisfaction. Using their own language, these women expressed their happiness and hope to achieve a better life. Fate is used as self-defense, self-persuasion, and excuses when dealing with stressful life events. Women in this study used „muhasabah‟ to improve their self and be a better person. This interview study is part of survey research of single mothers in Samarahan, Sarawak. The interviews were conducted from May to June 2001 at selected villages in Samarahan. Results had shown that most of single mothers described life satisfaction and happiness in terms of fate, role fulfillment, and a good social interaction. In spite of their ongoing difficulties and stigmas on their marital failure, these women put an effort to improve their social interactions and avoid any societal conflicts. It is clear that these women accept their roles as primary caregivers and lives with modesty, honor and dignity